Genetic and Environmental Contributions to Cotton Yield and Fiber Quality in the Mid‐South. Issue 1 (1st January 2019) - Raper, Tyson B.; Snider, John L.; Dodds, Darrin M.; Jones, Andrea; Robertson, Bill; Fromme, Dan; Sandlin, Tyler; Cutts, Trey; Blair, Ryan
Abstract : Producers need to know the contributions of genotype, environment, and their interaction (G×E) in determining cotton ( Gossypium hirsutum L.) lint yield, lint percentage, and fiber quality. The recent introduction of longer upper half mean length (UHML) fiber, lower micronaire cultivars may alter previously defined contributions. The objectives of this research were to define the genotype, environment, and G×E contributions to lint yield, lint percentage, and fiber quality from common cultivars evaluated within the US Mid‐South and define shifts in these contributions caused by the introduction of a longer UHML, lower micronaire cultivar. Data from 102 large‐plot trials within Alabama, Arkansas, Louisiana, Mississippi, Missouri, and Tennessee were compiled from the 2015 and 2016 seasons; 85 site‐years contained three common cultivars, and 69 contained four common cultivars. Analysis of three common cultivars within the 69‐site‐year dataset indicated environment dominated factors of lint yield (85.8%), lint percentage (88.5%), micronaire (70.9%), length (70.5%), and uniformity (70.4%). Large increases in the contribution of genotype to micronaire (26.0%) and length (37.6%) were observed when the lower micronaire, longer UHML cultivar was included. The relatively minor role of cultivar in determining lint yield and the substantial role of cultivar in determining micronaire and length suggest that producers within the Mid‐South should begin to place more importance on fiber quality data when selecting cultivars.